The Uses of Honorifics by President Candidate in The Campaign News Text on National Newspapers - Mukti Widayati (Universitas Veteran Bangun Nusantara, 2020)
The research aims to describe the types of linguistic tools for honorary excretion by presidential candidates in Indonesian newspaper news texts. The research method uses a qualitative approach. The data is in the form of direct sentence except from news texts that contain honorific expressions. Sources of data in the form of text national news about the presidential election campaign in the media Kompas, Media Indonesia, Republika, Sinar Harapan, and Sound Pembaharuan, published between January-March 2019. The collecting data is done by recording, clicking classify the linguistic tools used by taking fragments of sentence quotes. Data processing is done by identifying, sorting, verifying, interpretation of data, and concluded. The results of the study can be concluded that the types of linguistic tools for honorific expression in the speech of presidential candidates in Indonesian newspaper news texts include 13 types, namely: (a) self-name reference and self-name greeting, (b) self-name reference and self-name greeting as well, (c) greetings of kinship, (d) greetings of personal pronouns, (e) personal pronouns, (f) greetings of social position (social deixis), (g) position references/ranks / professions / social positions, (h) fatis, ( i) passive speech forms in-, (j) expressive modalities, (k) self-defeats, (l) euphemisms, and (m) relational modalities. The limitation of this research is that it still needs to be revealed the factors that influence honorifics, strategies that bring up honorifics, aspects of positive faces and negative faces. The study only focused on the type of use of honorific expressions